Design and Implementation of a Graphic 3d Simulator for the Study of Control Techniques Applied to Cooperative Robots - Urrea-Onate, E (Institute of Control, Robotics and Systems, 2015)
A new methodology is proposed for the design and implementation of three-dimensional simulations of manipulator robots, in individual as well as cooperative tasks, using several programming and 3D-design tools. To obtain easily the dynamic-mathematical models of movement for the represented systems, regardless of the kind of manipulator robot to be considered, the development of a computer algorithm is also presented. Besides, through the use of the Bullet library, we incorporated the detection of collisions between constitutive elements of the system, considering elements external to the robots, collisions between links of the same robot, or between two robots. Using a C++ programming platform, we also designed and implemented a flexible and intuitive graphic user interface. The dynamic-mathematical performance of the cooperative interaction between two actual robots, designed and implemented in the Departamento de Ingeniería Eléctrica of the Universidad de Santiago de Chile (DIE-UdeSantiago de Chile), was modeled, plotted and three-dimensionally simulated, by using the new algorithm proposed for this purpose. Finally, the performance results are presented and analyzed. © 2015, Institute of Control, Robotics and Systems and The Korean Institute of Electrical Engineers and Springer-Verlag Berlin Heidelberg.